Intervensi Suplemen Ibu Hamil dalam Mencegah Stunting : A Systematic Review - Rice Mandowa; Kadek Ayu Erika; Syahrul (LPPM Hang Tuah Pekanbaru, 2022)
Supplements for pregnant women are one of the treatment strategies that have important benefits in fulfilling the nutrition of pregnant women with poor nutrition in increasing fetal growth. One strategy for handling stunting cases at an early age is with additional interventions that can have an impact on reducing stunting cases. The purpose ofthis study was to systematically review the intervention of pregnant women with supplements and their benefits in preventing stunting. This systematic review was conducted using the 2009 PRISMA checklist. This study used databases namely PubMed, Cochrane Library, Springer Link, Base. The inclusion criteria for this study were English articles with a randomized controlled trial design (RCT) published in the last 10 years. This study found that seven studies met the inclusion criteria. Supplement interventions for pregnant women are divided into three types of supplements, namely lipid-based nutritional supplements (LNS-SQ), zinc supplements, and protein-energy food supplements that can be used as stunting prevention interventions. The LNS-SQ intervention can increase fetal growth but it is necessary to consider the intervention procedure and dose, content of supplements, and side effects of the intervention. The supplement intervention uses a holistic community approach strategy that has a positive impact on stunting prevention.